1995
DOI: 10.1111/j.1365-2621.1995.tb01947.x
|View full text |Cite
|
Sign up to set email alerts
|

Yield and storage stability of patties from pre‐rigor beef previously dipped in potassium sorbate and ginger solutions

Abstract: Pre-rigor beef strips dipped for up to 3 min in solutions of 2% ginger, 4% potassium sorbate or both were minced and made into patties. Meat yield before frying did not increase, but after frying the cooked pattie yield did increase with the mixed treatment. Yield increase was greatest with microwave cooking. There were no significant effects on pH, free fatty acids or TBA values, but slightly reduced total aerobic plate counts with the sorbate treatments when patties were stored at 5-7°C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…(1996) also reported that meat cuts and chicken carcasses when sprayed with acetic acid and lactic acid and GRE, garlic and onion, singly or in combination, extended shelf life at ambient temperature. Negbenebor et al. (1995) also reported that the use of GRE in beef patties reduced the psychotropic aerobic counts during their storage at 5–7C for 6 days.…”
Section: Resultsmentioning
confidence: 94%
“…(1996) also reported that meat cuts and chicken carcasses when sprayed with acetic acid and lactic acid and GRE, garlic and onion, singly or in combination, extended shelf life at ambient temperature. Negbenebor et al. (1995) also reported that the use of GRE in beef patties reduced the psychotropic aerobic counts during their storage at 5–7C for 6 days.…”
Section: Resultsmentioning
confidence: 94%
“…The addition of potassium sorbate to emulsified meat balls significantly affect the post-storage TBARS (p<0.05). Beef patties with 4% potassium sorbate also had no significant effect on TBARS values ( Negbenebor et al, 1995 ). By contrast, ground buffalo meat preblended with 0.3% potassium sorbate showed lower TBARS values than the control on days 0 and 8 of storage ( El-Aal, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…Kolsarici and Candogan (1995) reported that potassium sorbate treatment resulted in decreases in bacterial counts and high TBA values in vacuum-packed chicken leg and breast meats during storage at 3-5°C. Negbenebor, Balami, and Igene (1995) made beef patties with pre-rigor beef strips which had been treated with 4% potassium sorbate. They indicated that the treatment had no significant effect on TBA values, but slightly reduced total aerobic plate counts when the patties were stored at 5-7°C.…”
Section: Resultsmentioning
confidence: 99%